The development of the Vrancea Village in the context of European Union - Liviu Burghelea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Rural areas had represented for Romania cradle of civilization and prosperity, the convergence place for social, cultural and economic activities with complex implications on the Romanian reality. Tifesti commune, located in the Northeast of the Vrancea County will depend in the near future on the European funds for the development of agricultural activities, non-agricultural, services, the tourism potential developing of the area by promoting activities in winery.
Keywords: 330; rural area; social convergence; European funds; Vrancea County